Usability evaluation of hospital websites in Nigeria: what affects end users’ preferences? - O. Raji, Shakirat; Mahmud, Murni; Md. Tap, Abu Osman; Abubakar, Adamu (Springer International Publishing, 2014)
Hospital providers need to deliver satisfactory services in a specialized field which involves a great number of stakeholders with different concerns, needs and requirements. Some hospitals’ policies have been focused on providing health and medical services to the public. Less attention has been given to the responsibility to provide useful, accurate health information of high quality to their key publics mainly by facilitating interactive communication with patients, citizens and physicians and community services. To date, hospitals are turning increasingly towards the Internet and have developed their own web presence in order to enhance interactive communication practices. The research evaluated the usability of hospital websites in Nigeria, focusing on two websites in south- west of the country. Evaluation criteria for assessment were developed. The results provided empirical evidence that websites should be easy to use as well as aesthetically pleasing but must be rich in information content.